Sustainable biocatalysis: exploring the CO2 fixation activity of an alpha-keto acid decarboxylase - Hamzavinejad Moghaddam, Parisa (2021)
Carbon dioxide (CO2) is the major greenhouse gas formed from fossil fuels. The development of efficient and sustainable CO2 fixation reactions for the conversion of this waste gas into useful chemicals is one of the most important challenges of current chemistry. The aim of this thesis is to show the application of pyruvate decarboxylase from yeast, Saccharomyces cerevisiae (ScPDC) for the fixation of CO2 on its own or in an artificial enzyme cascade to produce key chemical platforms. Firstly, ScPDC was cloned, expressed and purified. The carboxylase activity of ScPDC to convert aldehydes to their corresponding 2-ketoacids was investigated with the carbonate buffer providing a source of CO2. Since the carboxylation reaction of ScPDC in the carbonate buffer failed to generate any 2-ketoacids, namely pyruvate or 2-ketobutryic acid, branched chain decarboxylase from Lactococcus lactis, LlKdcA was employed. LlKdcA also failed to show any carboxylase activity in carbonate buffer. To overcome the unfavoured carboxylation reaction and shift the position of the equilibrium towards 2-ketoacid formation, a transaminase enzyme was coupled to the carboxylation reaction. In the cascade the transaminase enzyme should selectively aminate the product of the carboxylation reaction, and not the aldehyde which is the substrate for the carboxylation reaction. For this purpose, commercially available